Experimental and theoretical high pressure study of calcium hydroxyaluminate phases. (July 2017) - Cuesta, A.; Rejmak, P.; Ayuela, A.; De la Torre, A.G.; Santacruz, I.; Carrasco, L.F.; Popescu, C.; Aranda, M.A.G.
Abstract: Five calcium hydroxyaluminate phases have been investigated by synchrotron powder diffraction at high-pressure: two hydrogarnets, kuzelite, stratlingite and ettringite. The obtained bulk modulus, K 0, for kuzelite, stratlingite and ettringite were 23(1), 27(1) and 30(3) GPa, respectively. Kuzelite and stratlingite underwent transformations above 1 GPa likely releasing interlayer water. Kuzelite becoming markedly amorphous and stratlingite remained crystalline, K 0  = 58(6) GPa in the 1.5–5.5 GPa pressure range. The structural behavior for hydrogarnet samples is prone to the use of pressure transmitting media. K 0 for Ca3 Al2 (OH)12 was 81(2) and 76(2) GPa for silicone oil and alcohol mixture, respectively. A similar study for Ca3 Al1.7 Fe0.3 (OH)12 yielded 73(1) and 58(1) GPa for silicone oil and alcohol mixture, respectively. Atomistic calculations using periodic Density Functional Theory showed that the softening in iron-doped katoite, when compared to stoichiometric katoite, can be assigned primarily to greater compressibility of CaO dodecahedra, which overcompensates strengthening of hydrogen bonding between Al/Fe hydroxide groups.